The Effectiveness of Acceptance and Commitment Therapy on Weight Loss and Cognitive Emotion Regulation in Obese Individuals - Azadeh Yaraghchi; Farhad Jomehri; Mohammadreza Seyrafi; Adis Kraskian Mujembari; Gholamreza Mohammadi Farsani (Iranian Association of Health Education and Health Promotion, 2019)
Background and Objective: This study assessed the efficacy of Acceptance and Commitment Therapy (ACT) on weight loss and cognitive emotion regulation in obese people. Methods: To do this study, 29 obese people with BMI > 29.9 were selected by purposeful sampling at the beginning, who completed demographic questionnaire and emotional cognitive regulation questionnaire. The participants' body mass index (BMI) was measured at the first meeting and at the end of the treatment. Participants were assigned into the intervention and the control groups. The intervention group participated in acceptance and commitment group therapy sessions for five months and at the end of the treatment sessions, they completed the questionnaires again. Statistical methods included Chi-square test, t-test for comparing two independent groups and analysis of covariance (P<0.01). Results: The findings showed that the acceptance and commitment therapy can reduce BMI; it also reduces negative strategies and increases the positive strategies of emotional cognitive regulation (P<0.01).  Conclusion: The present study showed that the acceptance and commitment group therapy resulted in weight loss and improved emotion regulation in people with obesity. Therefore, it is recommended to use this therapeutic approach for obese individuals.